Satureja musadaghensis (Lamiaceae) a new species from Türkiye - Ilçim, Ahmet (Phytotaxa, 2026)
Satureja musadaghensis İlçim sp. nov. is described from Hatay, Türkiye. Satureja musadaghensis confined to C5 square Hatay in southern Anatolia according to  Davis’ grid square system where it flowers late in the year (November) and grows on rocky slopes and under the Quercus cerris shrubs. The diagnostic morphological charecteristics are discussed and compared with those of closely related taxa. This new species distinguished from related species by elliptic-sphatulate leaves, upper ones with 1–3 pairs teeth towards to apex, and bigger bracts and calyx.